1995
DOI: 10.1103/physrevlett.75.3874
|View full text |Cite
|
Sign up to set email alerts
|

Are Nanophase Grain Boundaries Anomalous?

Abstract: The grain boundary regions of nanophase Cu metal are investigated using the x-ray absorption fine structure (XAFS) technique. Typical samples made by standard techniques need to be greatly thinned if measured in transmission in order to eliminate experimental artifacts which erroneously lower the apparent coordination number. To avoid this problem the samples were measured by the total electron yield technique. The results indicate a grain boundary structure which, on the average, is similar to that in convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 19 publications
7
57
2
Order By: Relevance
“…The pair-distribution functions, nearest-neighbor coordinations, and bond-angle distributions in the interfacial regions of n-SiC are found to be similar to those of bulk amorphous SiC. These results are consistent with neutron and X-ray diffraction measurements, and also with electron microscopy studies [49].…”
Section: Nanophase Silica and Silicon Carbidesupporting
confidence: 79%
“…The pair-distribution functions, nearest-neighbor coordinations, and bond-angle distributions in the interfacial regions of n-SiC are found to be similar to those of bulk amorphous SiC. These results are consistent with neutron and X-ray diffraction measurements, and also with electron microscopy studies [49].…”
Section: Nanophase Silica and Silicon Carbidesupporting
confidence: 79%
“…structure is similar to that in coarser-grained materials [20][21][22][23][24][25][26][27][28][29][30], while others proposed a frozen 'gaslike' structure of the grain boundaries in which the atomic arrangement at interfacial region lacks short-or long-range order [31][32][33]. In nanocrystalline solids a large fraction of atoms are located near grain boundaries.…”
Section: Nanostructurementioning
confidence: 92%
“…The intergrain regions could also be amorphous in nature, which would clearly produce an attenuation of the EXAFS signal and a reduction of the peak amplitudes in the Fourier transform. However, the qualitative effect in EXAFS is the same as that produced by the simple reduction of crystallite size, and care has to be taken over the sample preparation and measurement procedures as on the EXAFS analysis to separate the two effects, 29,32 as illustrated in the current controversy over the level of disorder in the intergrain regions in the case of nanocrystalline metals. [32][33][34][35] In this respect, Qi et al reported in their EXAFS study of nanocrystalline YSZ that the cation-cation (Zr-Zr) coordination number is reduced due to the large number of cations near the surface (with fewer nearest neighbors) when the grain size decreases.…”
Section: A Xanes: Qualitative Analysismentioning
confidence: 99%